2010
DOI: 10.1091/mbc.e09-09-0767
|View full text |Cite
|
Sign up to set email alerts
|

The Na+/H+Exchanger NHE6 in the Endosomal Recycling System Is Involved in the Development of Apical Bile Canalicular Surface Domains in HepG2 Cells

Abstract: This study underscores the emerging role of NHE6 as a novel regulatory protein in the apical surface development of human hepatoma HepG2 cells. A limited range of endosomal pH facilitated by NHE6.1 is suggested to be important for securing the polarized distribution of membrane lipids and proteins and maintenance of apical bile canaliculi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 40 publications
4
61
0
Order By: Relevance
“…9D). These results indicate that Nhx1p contributes to the regulation of endosome luminal pH by means of proton leakage from the endosome, as do organellar NHEs in mammalian cells (24,25). Lowering the pH of the endosome lumen would not account for the impaired MVB formation in nhx1⌬ cells because MVB formation observed in vitro was enhanced by acidic pH, as shown in Fig.…”
Section: Endosomal Na ϩ /H ϩ Exchange Activity Is Required For Efficimentioning
confidence: 74%
See 1 more Smart Citation
“…9D). These results indicate that Nhx1p contributes to the regulation of endosome luminal pH by means of proton leakage from the endosome, as do organellar NHEs in mammalian cells (24,25). Lowering the pH of the endosome lumen would not account for the impaired MVB formation in nhx1⌬ cells because MVB formation observed in vitro was enhanced by acidic pH, as shown in Fig.…”
Section: Endosomal Na ϩ /H ϩ Exchange Activity Is Required For Efficimentioning
confidence: 74%
“…Although NHE1-5 are mainly found in plasma membranes, NHE6 -9 are mainly distributed to organellar membranes. We have shown previously that in mammalian cells Na ϩ /H ϩ exchangers contribute to endosomal pH homeostasis by allowing proton leakage from the endosomal lumen in cooperation with V-ATPase activity (23)(24)(25)(26). The budding yeast S. cerevisiae also expresses Na ϩ /H ϩ exchangers, one of which, Nhx1p, localizes to the late endosomes (prevacuolar compartment) and is highly homologous to the NHEs found in mammalian cells (27,28).…”
mentioning
confidence: 99%
“…Knockdown of RACK1 increases NHE6 levels in endosomes, elevates endosomal pH, and disturbs transferrin uptake (29). Previously, we reported that knockdown or overexpression of NHE6 in hepatoma HepG2 cells disturbs endosomal pH and polarized membrane traffic, and that consequently it causes a reduction in the number of apical bile canalicular surface domains (30). These studies suggest that NHE6 plays important roles in the maintenance of membrane traffic in endosomal compartments via pH regulation.…”
Section: CLmentioning
confidence: 86%
“…Another important function of NHE6 was demonstrated in hepatoma HepG2 cells, where NHE6 localizes to recycling endosomes and colocalizes with transcytosing bulk membrane lipids [122]. Knock-down of NHE6 lowered recycling endosomal pH and surprisingly, disrupted the apical canalicular plasma membrane with failure to traffick or maintain apical proteins; these effects were associated with reduced abundance of apical lipids.…”
Section: Slc9a6 -Nhe6mentioning
confidence: 99%
“…Knock-down of NHE6 lowered recycling endosomal pH and surprisingly, disrupted the apical canalicular plasma membrane with failure to traffick or maintain apical proteins; these effects were associated with reduced abundance of apical lipids. Thus, in HepG2 cells endosomal NHE6 is important for maintaining the polarized distribution of membrane lipids at the apical surface, the maintenance of apical bile canaliculi and consequently cell polarity [122]. In addition to cell polarity, NHE6 participates in clathrin-dependent endocytosis by alkalinizing clathrin containing early endocytic vesicles [179].…”
Section: Slc9a6 -Nhe6mentioning
confidence: 99%